Obesity: Familiarity and Unhealthy Lifestyle - Vici, Giorgia; Belli, Luca; Ceci, Roberto; Cesanelli, Leonardo; Polzonetti, Valeria (Progress in Nutrition, 2018)
Obesity in now defined as “epidemic” due to the presence of a high prevalence with a steady increase of cases. The aim of this study was to investigate alimentary habits and anthropometric measurements referring to children aged 8 years attending public (state) schools in 2004 and 2015 in Fabriano (AN) located in Le Marche region in Italy and their parents. Data were collected using anthropometric techniques and Food Frequency Questionnaire in 2004 and 2015 in studied population (students and parents). Body Mass Index (BMI), food habits and level of physical activity were used to investigate nutritional status. In 10 years, it was observed that overweight children decreases from 27% to 24% and that children with parents overweight/obese have more probability to be overweight/obese, both in 2004 and 2015. Children daily breakfast consumption significantly increases from 80% to 92%. Physically active children increases from 20% to 46%. The analysis of the obtained data shows that, even if it is possible to observe slightly improvements, the problem of overweight and obesity presence, in particular in children, is relevant and represent a true social problem.